Mosquito-larvicidal efficacy of gold nanoparticles synthesized from the seaweed, Turbinaria ornata (Turner) J.Agardh 1848. (17th November 2018) - Deepak, Paramasivam; Sowmiya, Rajamani; Balasubramani, Govindasamy; Aiswarya, Dilipkumar; Arul, Dhayalan; Josebin, Muthu Paulraj Diviya; Perumal, Pachiappan
ABSTRACT: Malaria is considered a dreadful mosquito-borne infectious disease of human beings caused and spread by biting of the female mosquito Anopheles stephensi infected with a parasitic protozoan Plasmodium falciparum . Continuous application of chemicals/synthetic insecticides for vector control causes various problems such as resistant mechanism of mosquito, toxicity to nontarget aquatic organisms and disturbance to the microbial community of the soil. Currently, green synthesized nanoparticles are being employed in various biological processes including insect and pest control. The present investigation focused on the mosquito-larvicidal property of Turbinaria ornata- mediated gold nanoparticles (To-AuNPs) and its boiled aqueous extract (To-AE) against the malarial vector A. stephensi . The recorded lethal concentration (LC50 and LC90 ) values (µg/ml) of To-AE and To-AuNPs against fourth instar larvae of A. stephensi were 37.77 and 159.55 and 12.79 and 78.70, respectively. The To-AuNPs were characterized through UV-visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), energy dispersive x-ray spectroscopy (EDX), zeta potential and dynamic light scattering (DLS) method. The presently synthesized gold nanoparticles through the single-step, eco-friendly method is a potentially effective mosquitocidal agent.